The Determinants of Survival Time of Premature Neonates at Shambu General Hospital - Olani Debelo (Advances in Public Health)
Background. Premature birth occurs before 37 completed weeks of gestation. It has a greater risk of developmental disabilities, health, and growth problems than full birth. It is the second leading cause of morbidity and mortality among under-five children. Therefore, the aim of this study was to identify determinants of the survival time of premature neonates admitted to the neonatal intensive care unit (NICU) at Shambu General Hospital. Methods. A retrospective study design was used. Data were collected from medical records of premature neonates from January 2018 to March 2021. A total of 361 premature neonates were included in the study. Descriptive statistics, Kaplan–Meier (KM) curve and log-rank test were computed. The survival time of preterm neonates were compared for different categorical covariates. The Cox’s proportional hazard model was fitted. The fitness and statistical assumptions of the model were checked. Parametric regression models were compared. Weibull regression model was fitted for premature data to identify the predictors of death time of the premature neonates. Results. The proportion of premature neonatal death was 23.3%. Gestational age, neonatal sex, place of residence, hemoglobin (Hb) level, hypertension status, HIV status, antenatal care, mode of delivery, birth weight, multiple pregnancies, perinatal asphyxia, and parity greater than 1 were significantly associated with the death time of premature neonates. Conclusion. Percentage of premature neonatal death in this study was 23.3. Improving mothers’ Hb level through routine iron supplementation, encouraging mothers to have regular antenatal follow-up at health institution were recommended.